Hsa_circ_0026782 Acts as a “Molecular Break” of CREB1‐Mediated Transcription by Promoting Its Phosphorylation at Ser142 That Prevents Keloid Progression - Zhong, Xin‐Cao; Chen, Chun‐Ye; Feng, Zi‐Xuan; Wang, Yong; Zhang, Tao; Zhuang, Ze‐Ming; Wu, Zhang‐Rui; Du, Yong‐Zhong; Chen, Jun; Lin, Xiao‐Ying; Tan, Wei‐Qiang (Advanced science, 2025)
Keloids are a form of excessive fibrosis disease characterized by tumor‐like features, which are prone to recurrence. Circular RNAs play a role in various diseases, but its roles in keloids remain unclear. In this study, using high‐throughput RNA sequencing to compare keloids with normal scars, a novel circRNA, hsa_circ_0026782 is identified, whose expression is downregulated in keloids. The hsa_circ_0026782 inhibits the proliferation, migration, invasion, and apoptosis of primary human keloid fibroblasts, blocks the cell cycle in the S phase in vitro, and prevents keloid progression in vivo. Mechanistically, 1–90 nucleotides of hsa_circ_0026782 directly bind to the transcription factor CREB1. This interaction increases the exposure of the basic leucine zipper domain of CREB1 to enhance its dimerization. In addition, this interaction also promotes CREB1 phosphorylation at serine residue 142, inhibits the binding of CREB1 to the promoters or enhancers of its downstream target genes, and ultimately alters the transactivation of CREB1. The findings unveil that the hsa_circ_0026782/CREB1 axis acts as a transcriptional spatiotemporal “molecular break” in the formation of keloids, providing a new target for the therapy of keloids.